Growth and Yield Response of Black Rice (Oryza sativa L.) to Lamtoro Leaf Liquid Organic Fertilizer and NPK - Utami, Sri; Fitria, Fitria; Alwi, Mukhaddat (AGRIUM: Jurnal Ilmu Pertanian, 2026)
Rice is the main source of carbohydrates, black rice is a rich source of bioactive compounds. Increasing rice yields can be done by providing organic and inorganic fertilizers. Lamtoro leaves as a liquid organic fertilizer (LOF) contain essential nutrients, as well as NPK. This study aims to evaluate the growth and yield response of black rice to liquid organic fertilizer and NPK. This study used a Randomized Block Design (RBD) with 2 factors, namely LOF of Lamtoro leaves (100 ml/plot, 200 ml/plot, and 300 ml/plot) and NPK Fertilizer (0 g/plant, 1.5 g/plant, 3 g/plant, and 4.5 g/plant). Parameters observed were plant height, chlorophyll leaf, number of tillers per hill, number of productive tillers, number of panicles, grain weight per panicle, 1000 grain weight and root volume. The data analyzed by analysis of variance (ANOVA). The research results showed that liquid organic fertilizer of lamtoro leaves had no significant effect on all parameters of black rice plants. Fertilizer NPK had significant effect on the parameters of plant height and number of tillers per hills, the number of productive tillers and the number of panicles. NPK significantly influenced growth parameters while the liquid organic fertilizer showed no significant effect.